Maternal mortality at the V Lima Ciudad Health Division. 2000-2004 - Belmont, Talía Liliana (2015)
OBJETIVE: To evaluate maternal mortality in the Department of Health V Lima City (DVLC). Calculate the maternal mortality ratio (MMR). Sort maternal mortality (MM) as direct or indirect, avoidable or unavoidable. Identify contributing factors. The presence of delay in care and the stage in which it occurred. MATERIALS AND METHODS: Retrospective descriptive study that included all cases of MM recorded in the files of the DVLC for 2000-2004. Data were obtained from the records of epidemiological research at MM and, if necessary, the summary of medical records. To analyze the data for the years 2003 and 2004 was used by underreporting during the years 2000 to 2002. RESULTS: MMR was 100.63; 66.7% were direct MM. Gestational hypertension was responsible for 50% of these deaths, followed in frequency abortion, infection and bleeding. The most common contributory factor was staff (34%). There was delay in care in 57% of cases and 54% patients were not transferred. Approximately 50% of MM was avoidable. CONCLUSIONS: MM remains a major problem in our country whose analysis is dented by high underreporting. Health policies that improve prenatal care, quality of care and hospital infrastructure, and knowledge of the problem is required, if we decrease the TMM.